ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI BELANJA MODAL - Afrilin Kristiani, - (2020)
This study aims to determine the effect of Regional Revenue, General Allocation Funds, Special Allocation Funds, and Financing Surplus Budget on capital expenditure. The object of this research are regencies and cities throughout Indonesia. The sample used in this study amounted to 506 regencies and cities throughout Indonesia in 2018. The sampling technique used was the purposive sampling method with predetermined criteria. The data used in this study are secondary data from the Regional Government Financial Reports published by the Supreme Audit Board. Hypothesis testing in this study is multiple linear regression analysis using SPSS 24 and a significance level of 5%. The results of the research partially show that the Regional Original Revenue has a positive effect on capital expenditure with a significance level of 0.003, the General Allocation Fund has a positive effect on capital expenditure with a significance level of 0,000, the Special Allocation Fund has a positive effect on capital expenditure with a significance level of 0,000, and the Remaining Over Budget Financing a positive effect on capital expenditure with a significance level of 0,000.